Teacher's Strategies in the Classroom Setting: Integrating Local Culture into English Language Teaching - Herdi Herdi; Ribut Wahyu Eriyanti; Atok Miftakhul Huda (ELT-Lectura, 2023)
Some teachers have a lot of strategies in the learning and teaching process in English class, but only a few teachers link local culture into the learning process in their class, meanwhile the teacher's strategies is an important role in improving students' ability to learn English containing local culture. The design used in this research is a type of narrative inquiry research with a qualitative approach. which is held in the intensive course class of the faculty of teacher training and education in January 2022. The subject of this research is an English teacher who teach in the intensive class at the Faculty of Education and Vocational Studies, Universitas Lancang Kuning. Then, the data from the observations and interviews were analyzed. Based on the results of the interview, the teacher applies information about local culture into eight techniques or strategies; brainstorming, contextualizing topics, conducting class discussions, creating video projects, looking for references/literature, designing lesson syllabus, selecting textbooks, drilling topics. The researcher found that these techniques had an impact on increasing students' ability to learn English with local culture. The findings of this study revealed that bringing local culture in English language teaching gave a significant effect on the students' ability in learning English with local culture at intensive course class. The idea of ​​bringing local culture in the classroom was in line with the implementation of Contextual Teaching and Learning approach. During the teaching and learning process, the students not only learned a foreign language but also became aware of preserving their local culture.